A review of electromechanical actuators for More/All Electric aircraft systems. (November 2018) - Qiao, Guan; Liu, Geng; Shi, Zhenghong; Wang, Yawen; Ma, Shangjun; Lim, Teik C
Conventional hydraulic actuators in aircraft systems are high maintenance and more vulnerable to high temperatures and pressures. This usually leads to high operating costs and low efficiency. With the rapid development of More/All Electric technology, power-by-wire actuators are being broadly employed to improve the maintainability, reliability, and manoeuvrability of future aircraft. This paper reviews the published application and development of the airborne linear electromechanical actuator. First, the general configuration, merits, and limitations of the gear-drive electromechanical actuator and the direct-drive electromechanical actuator are analysed. Second, the development state of the electromechanical actuator testing systems is elaborated in three aspects, namely the performance testing based on room temperature, testing in a thermal vacuum environment, and iron bird. Common problems and tendencies of the testing systems are summarized. Key technologies and research challenges are revealed in terms of fault-tolerant motor, high-thrust mechanical transmission, multidisciplinary modelling, thermal management, and thermal analysis. Finally, the trend for future electromechanical actuators in More/All Electric Aircraft applications is summarized, and future research on the airborne linear electromechanical actuators is discussed.